Solutions of Weakly-Perturbed Linear Systems Bounded on the Entire Axis - Boichuk, А. A.; Boichuk, О. A.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We establish conditions under which solutions of weakly-perturbed systems of linear ordinary differential equations bounded on the entire axis R emerge from the point ε = 0 in the case where the corresponding unperturbed homogeneous linear differential system is exponentially dichotomous on the semiaxes R + and R −.